Abandonment trauma from a developmental perspective and its treatment - Martínez, Borja Luque (Seven Editora, 2023)
Human beings are acquiring learning as we live different experiences. These learnings together with biological factors condition our development. In favorable contexts we will achieve greater development of our potential, however, in unfavorable contexts, our capacities may be reduced. Even situations of special impact may occur throughout the life of the person, which leaves their mark and blocks the proper development of the person. These are traumatic situations that reduce learning capacity and generate palpable biopsychosocial damage, something that happens in cases of early abandonment. DOI: https://doi.org/10.56238/methofocusinterv1-041